2018
DOI: 10.15547/tjs.2018.s.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Hospital staff readiness for disaster medical support

Abstract: Last decades increase in both disasters' frequency and severity have been recorded globally. Discrepancy between the available and required medical means and capabilities in the area of damage leads to increase of the workload of the hospitals in vicinity. The aim of this study is to analyze hospital staff readiness in case of disaster. In order to achieve the set goal 5-question dichotomous survey was performed between 54 hospital professionals. The questions of our survey are focused on knowledge about hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The incidence of disasters has increased in recent years due to various reasons including climate change, thereby increasing the severity of the disasters, which have caused significant damage to individuals and communities (Baker et al 2019;Georgieva et al 2018;Labrague et al 2016;€ Oztekin et al 2016). As a result of the increased severity of disasters worldwide, nurses' role in patient care during disasters have been further emphasized (Labrague et al 2018), and there is a growing need for enhancing nurses' disaster response competencies (Loke & Fung 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of disasters has increased in recent years due to various reasons including climate change, thereby increasing the severity of the disasters, which have caused significant damage to individuals and communities (Baker et al 2019;Georgieva et al 2018;Labrague et al 2016;€ Oztekin et al 2016). As a result of the increased severity of disasters worldwide, nurses' role in patient care during disasters have been further emphasized (Labrague et al 2018), and there is a growing need for enhancing nurses' disaster response competencies (Loke & Fung 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A disaster is defined as 'a serious disruption of the functioning of a community or a society at any scale due to hazardous events interacting with conditions of exposure, vulnerability, and capacity, leading to one or more of the following: human, material, economic and environmental losses and impacts' (United Nations Office for Disaster Risk Reduction 2009). The rising incidence of disasters and the severity of damage thus caused (Baker et al 2019;Georgieva et al 2018) have led to growing demands for disaster response competencies among nurses who provide care for victims during a disaster (Loke & Fung 2014) Previous studies on nurses' disaster nursing competencies have reported that nurses' disaster nursing competencies are strongly associated with previous disaster care experience(s) and disaster-related training (Labrague et al 2018); therefore, it is important to develop effective training programmes to enhance nurses' disaster nursing competencies. In addition, a scoping review (Al Thobaity et al 2017) identified the following as the most common domains of core disaster nursing competencies: communication, decontamination and safety, planning, command system, and ethics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The world has been severely affected by the increasing prevalence of major disasters, such as earthquakes, floods, and tsunamis (Georgieva et al., 2018). Natural and man‐made disasters over the past two decades have resulted in more than 800 million casualties and severe economic losses amounting to more than $50 billion (Zarei, 2016).…”
Section: Introductionmentioning
confidence: 99%